PEMBERDAYAAN FORUM KERUKUNAN UMAT BERAGAMA KABUPATEN MAGELANG DALAM MENJAGA KONDUSIVITAS PEMILU SERENTAK 2019 - Apsari Wahyu Kurnianti; Anisa Arifina (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Universitas Muhammadiyah Cirebon, 2019)
Community service activities are carried out at the Harmony Forum Religious Community (FKUB) Magelang Regency which is carried out in the form of giving counseling and outreach to FKUB members who were seen as opinions leaders in their religious groups, stakeholders in government, academia and security forces. The target in this community service activity is counseling and socialization to FKUB members by providing anti-hoax learning with the material to Know and Prevent Hoax in the Digital Era in the Context of Election Simultaneously 2019. The output for extension and outreach participants is to be able to understand threats new issue brought about by the use of social media in religious issues, deep understanding using social media wisely, distinguishing hoaxes, can prevent acts of intolerance in religion and FKUB's declaration with stakeholders in the field the government, academics, and security forces of Magelang Regency to guard conductivity in the framework of 2019 Concurrent Elections. The material provided in the training of community service activities is a focus group discussion (FGD) to formulate a memorandum of understanding